PENGARUH KINERJA GURU TERHADAP HASIL BELAJAR SISWA DI SMP NEGERI 4 TANJUNG JABUNG TIMUR KOTA JAMBI - Resi Adelina Manullang (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
This study aims to determine, the effect of teacher performance on student learning outcomes SMP Negeri 4 especially teachers who are in Tanjung Jabung Timur Jambi. This research is descriptive qualitative by using the Likert scale questionnaire dissemination method by determining the variables, the indicators and formulate the items with each question. Qualitative research refers to research as a gathering tool to obtain the expected validity. Based on data analysis that was done with technical analysis, influence of teacher performance toward result of study at junior high school 4 Tanjung Jabung Timur Jambi, hence result of research indicate that influence of teacher performance toward result of student learning lead to significant by using formula Moment Product obtained tarithmetic > ttable Or 4,940.00 > 2,228.00, then the result of the research is stated acceptable.Keyword: teacher performance